Leadership Styles of Women Leaders in Panchayati Raj Institutions - Manmeet Kaur , Neelam Bhardwaj and L. S. Bareth, (Indian Journal of Extension Education, 2017)
Women leadership in Panchayati Raj Institutions (PRI) is crucial not only for the development of women themselvesbut also for the availability of their creative potential that is socially important and without which, the country cannothope for any sustainable development. This study was conducted in three districts of Uttarakhand State i.e. UdhamSingh Nagar, Dehradun and Tehri Garhwal districts on two hundred women leaders especially Pradhans who wereselected through census method. Data were collected with the help of semi-structured interview schedule. Thefindings of the study depict that there was very slight difference found in each category of leadership style.Authoritarian leadership style was more prominent in the Udham Singh Nagar whereas participative and delegativestyles were followed by women leaders who belonged to hill districts of Uttarakhand. Various socio-psychologicaland communication pattern characteristics were found positively and significantly related with leadership styles ofwomen leaders.